Immunization Practices in Children Presenting to Outpatient Department of a Tertiary Care Hospital - Bushra Feroz, Arshad Khushdil, Imran Ahmad Memon, Sadaf Nawaz, Maryam Shahzadi, Waqas Akhtar (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Immunization has tremendously reduced the incidence of childhood illnesses. Aim: To identify the causes of failure of immunization in our setups and help strengthen the EPI by solving those causes. Study design: Descriptive cross-sectional study. Place and duration of study: Department of Paediatrics, CMH Quetta from July 2022 to December 2022. Methodology: Two hundred and seven children (0-24 months) of both genders with acute diarrhoea passing three or more loose stools per day for no longer than two weeks were chosen. Using EPI cards, all parents of these patients were asked about their children’s vaccination status. The demographic information like name, age and gender were noted. Results: There were 104 (51%) females and 103 (49%) females with a mean age of 18±1.5 months. 91.8% received BCG and OPV0, about 82% received Penta +OPV1+Hib at 6 weeks and 157 children were vaccinated at 10 weeks. Complete vaccination was received by 137 children at the age of 14 weeks, 52% of the children received measles vaccine, however, only 32% of the children had received their second dose of the measles vaccine by the time they were 15 months old. Conclusion: The immunization practices in children were decreased with advancing age of the children. The vaccination rate was highest at birth, 6 weeks and 10 weeks but significantly reduced at 9 months and 15 months. A robust awareness campaign is needed in order to sensitize the parents regarding the immunization of their children particularly at 9 months and 15 months of age. Keywords: Immunization, EPI, Polio, Measles, Tuberculosis, Diphtheria